Optical Coherence Tomography Position Analysis of Retropupillary Iris-Fixated Intraocular Lens in Iris Tissue. (9th August 2022) - Riedl, Jana C.; Bopp, Michael R.; Gross, Charlotte F.; Vossmerbaeumer, Urs
Abstract : Purpose . The aim of this study was to evaluate a micrometer-accurate analysis of the retropupillary Verisyse® intraocular lens (IOL) (Ophtec, Groningen NL; Santa Ana, USA) enclavation in the iris tissue. Methods . A retrospective consecutive case series was conducted at the Department of Ophthalmology, University Hospital Mainz. Patients with an optical coherence tomography (Spectralis®, Heidelberg Engineering®; Heidelberg, Germany) examination after retropupillary Verisyse® IOL implantation were included retrospectively. The enclavation geometry was measured using the Eye-Explorer® from Heidelberg Engineering® (Heidelberg, Germany). Seventeen measuring positions were determined nasally and temporally at the corresponding enclavation points. Results . 72 eyes of 67 patients after implantation of a retropupillary Verisyse® IOL were analyzed. The average age was 68 ± 17.2 years (63% female; 38% male). The analysis of the position of the Verisyse ® IOL showed highly homogeneous data in all measured points. The depth of the anterior chamber showed a positive correlation with width of the posterior deflection of the iris tissue behind the enclavation (Pearson r : 0.321, p = 0.041 ). The offset of the haptics showed greater deviations, and the lens diopter implanted was higher ( r  = 0.337, p = 0.007 ). Conclusion . This is the first study that analysis the exact enclavation of retropupillary implanted Verisyse® IOL. It provides new information about the intrastromal course of the haptics in the iris tissue. It could be shown that the haptics do not run parallel in the iris tissue, but are anchored in the iris tissue with an average offset of 95  µ m. This rebuts previous assumptions about the intrastromal course and provides new information.